2021
DOI: 10.3390/languages6030124
|View full text |Cite
|
Sign up to set email alerts
|

Quality of L2 Input and Cognitive Skills Predict L2 Grammar Comprehension in Instructed SLA Independently

Abstract: Input is considered one of the most important factors in the acquisition of lexical and grammatical skills. Input has been found to interact with other factors, such as learner cognitive skills and the circumstances where language is heard. Language learning itself has sometimes been found to enhance cognitive skills. Indeed, intensive contact with another language has been found to sometimes boost cognitive skills, even in intensive instructed settings, such as immersion programs (bilingual advantage hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
1
7
1
Order By: Relevance
“…The rich and authentic language input that learners engage with during informal learning activities can stimulate these processes of intake just as well as the input received during classroom instruction. Books, games and videos in the target language stimulate many of those cognitive processes of engagement that are considered effective for foreign language learning as their neural correlates involve widespread brain regions as a function of rich perceptual environments (Li and Jeong, 2020;Kersten et al, 2023). While the resulting development of language proficiency might be small or large, it will reinforce or change existing schemas, instigating the learner's active construction of language knowledge and nudging them forward in the process of improving their interlanguage (Selinker, 1972;Kersten et al, 2023).…”
Section: Informal Learning In English As a Foreign Languagementioning
confidence: 99%
See 1 more Smart Citation
“…The rich and authentic language input that learners engage with during informal learning activities can stimulate these processes of intake just as well as the input received during classroom instruction. Books, games and videos in the target language stimulate many of those cognitive processes of engagement that are considered effective for foreign language learning as their neural correlates involve widespread brain regions as a function of rich perceptual environments (Li and Jeong, 2020;Kersten et al, 2023). While the resulting development of language proficiency might be small or large, it will reinforce or change existing schemas, instigating the learner's active construction of language knowledge and nudging them forward in the process of improving their interlanguage (Selinker, 1972;Kersten et al, 2023).…”
Section: Informal Learning In English As a Foreign Languagementioning
confidence: 99%
“…Books, games and videos in the target language stimulate many of those cognitive processes of engagement that are considered effective for foreign language learning as their neural correlates involve widespread brain regions as a function of rich perceptual environments (Li and Jeong, 2020;Kersten et al, 2023). While the resulting development of language proficiency might be small or large, it will reinforce or change existing schemas, instigating the learner's active construction of language knowledge and nudging them forward in the process of improving their interlanguage (Selinker, 1972;Kersten et al, 2023). These processes of cognitive-interactional language learning can be seen as the reason why activities such as interacting with others in on-line media, watching the latest YouTube video or gaming with peers in the target language can have a beneficial effect on learning.…”
Section: Informal Learning In English As a Foreign Languagementioning
confidence: 99%
“…Beyond cognitive skills (e.g., Kersten et al 2021) other learner factors, such as the language program, the students' gender, their language background and their educational background can serve as predictors of the students' L2 performance (e.g., Böhme et al 2016;Carr and Pauwels 2006;Gottburgsen and Gross 2012;Paradis 2011). In particular, the educational background is important, due to possible preselection effects as described above.…”
Section: Attention and L2 Grammarmentioning
confidence: 99%
“…In second language (L2) acquisition research, various factors have been shown to affect the acquisition of L2 grammar, and these have often been subdivided into childinternal factors (e.g., language aptitude, motivation and, of course, individual cognitive abilities, such as attention or intelligence) and child-external factors (i.e., L2 input quality and quantity (e.g., Kersten et al 2021;Paradis 2011;Unsworth et al 2015)). The purpose of this article is to examine the influence of two of these factors in instructed second language acquisition, i.e., L2 input quantity and young learners' cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Hopp et al (Hopp et al 2019) and Kersten et al (Kersten et al 2021) compared and contrasted early foreign-language learners' and monolingual children's comprehension looking for syntactic first-language transfer effects, input effects on syntactic development, and individual variations. They found that early learners have less stereotypes and the variation in acquisition is linked to phonological awareness.…”
Section: Introductionmentioning
confidence: 99%